Salmonella sp. Contamination in Broiler Chicken Meat at Gorontalo Central Market: A Quantitative Microbial Risk Assessment Approach - Tri Septian Maksum; Hazarul Aswad (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Gorontalo Central Market is the largest marketplace for broiler chicken meat sales in Gorontalo. Contamination of broiler chicken meat may occur during storage or at the point of sale (market) and can proliferate if the cooking process is inadequate. Laboratory test results revealed the presence of Salmonella sp. in broiler chicken meat at levels exceeding the maximum permissible limits for microbial contamination in food. This study aimed to assess the quantitative health risk posed by Salmonella sp. contamination in broiler chicken meat sold at Gorontalo Central Market. This was a descriptive observational study employing a Quantitative Microbial Risk Assessment (QMRA) approach. The study samples consisted of seven broiler chicken meat samples collected from seven meat stalls at Gorontalo Central Market and 85 consumers who purchased and consumed broiler chicken meat sold at the market. Respondents were selected using an accidental sampling technique. The results showed that broiler chicken meat sold at Gorontalo Central Market contained Salmonella sp. ranging from 1.4e3 to 3.0e5 CFU/g. Health risk assessment indicated that, among the seven meat stalls evaluated, five were classified as high-risk (Pinf/day/meal = 3.83–4.85), while two stalls were classified as no risk (Pinf/day/meal = 0). It is recommended that vendors improve sanitation practices at their selling locations and maintain proper personal hygiene to reduce the potential for pathogenic microbial contamination.